Conceptual justification of a new model of innovative modernization of the regional economy - Irina A. Naugolnova, Lidia P. Bazhutkina, Elena N. Korolyova, (Opción, 2019)
The study aims at identifying the processes of new regionalization that manifested in the economic space within the regions, when the economy at the corporate business structures level has a network character via developing mathematical models of complex socio-economic systems. The main results of the article will contribute to the formation of tools for testing the most progressive innovations aimed at the formation of the spatial organization of the territory. In conclusion, in the process of government management of sustainable development of the region, government programs have proven to be an effective tool for a program-targeted approach.